Impact of Financial Reports, Auditors, and Management on Food & Beverage Investments - Diah Rizki Syahrani Nasution; Yenni Samri Juliati Nasution; Laylan Syafina (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
Investment decisions are a process involving the assessment and selection of resource allocation into various types of assets or projects with the aim of achieving desired financial outcomes. The average investment decision phenomenon, proxied by the Price Earning Ratio (PER), shows a fluctuating pattern from 2019 to 2023. This study investigates how financial reports, independent audit reports, and management quality influence investment decisions in Indonesian food and beverage companies. By analyzing secondary data from financial and annual reports of companies listed on the Indonesia Stock Exchange from 2019 to 2023, this study uses a quantitative method. Data were obtained from 12 companies selected through purposive sampling during the 2019–2023 period, resulting in 60 observations. Investment decisions are treated as the dependent variable, while financial reports, audit reports, and management quality serve as independent variables. Data analysis was performed using regression with SPSS 27 software. The study reveals that financial reports have a significant impact on investment decisions, while management quality and audit reports do not. These findings highlight the crucial role of financial reports in investment decision-making, suggesting that investors should focus on financial data rather than evaluating management quality or audit reports.